The Analysis of Word Formation in Movie "Wonder" and Its Application in Teaching Vocabulary - Amelya Baiti Nur'aini; Juita Triana; Luana Fogli (Scripta : English Department Journal, 2021)
The aims of this research are to find out word formation in the movie entitled “Wonder” and to describe the application of word formation in movie “Wonder” to teach vocabulary. This research belongs to a descriptive qualitative research. The object is the movie entitled “Wonder”. The data of this study is word formation processes in the movie. To collect the data, the writers do some steps. Those are watching the movie, reading the movie script, and identifying the word formation processes. In analysing the data, the writers conduct some steps: identifying word formation processes in the utterances used by the main characters, classifying the data into types of word formation based on George Yule’s theory, and applying the finding to teach vocabulary. The result of this research shows that there are 148 word formations that are classified into ten types of word formation: 53 of compounding (36%), 5 of coinage (4%), 23 of borrowing (16%), 2 of blending (1%), 8 of clipping (5%), 3 of backformation (2%), 5 of conversion (4%), 2 of acronyms (1%), 45 of derivation (30%), and 2 of multiple processes (1%). The finding of this research can be applied in teaching vocabulary.